PARTISI FOTOSINTAT BEBERAPA KULTIVAR KEDELAI (Glicine max. (L.) Merr.) PADA ULTISOL - -, SARAWA; BACO, ABDU RAHMAN (Jurnal Agroteknos, 2014)
Soybean (Glycine max (L.) Merr.) is a legume plant that has high economic value containing 20 % fat and 40 % protein. Soybeans are used in a variety of industries, both for food industry and for livestock feed. This research aimed to determine the partition of photosynthates of some soybean cultivars on Ultisol of Poasia, Anduonohu in 2013. The experiment was conducted using polybags filled with 15 kg top soil that had been dried for 2 days. The experiment was conducted using 10 treatments (cultivars) and repeated 3 times so there were 30 experimental units. Each experimental consisted of 12 polybags so there were 360 polybags. Four seeds were sown in each polybag, and thinning was performed at the age of 2 weeks and left only two crops to grow. The research results showed that each cultivar has different photosynthate partitioning. In general, all cultivars provided the highest photosynthate partitioning to leaves and stems until the age of 75 day after planting during the vegetatif phase and into flowers and pods on the generatif phase. Burangram cultivar provided the highest photosynthate partitioning into the pods followed by cultivars Argomulyo, Grobogan, and Kaba.